Conjuring a Supernatural Product – DelMarine - Wan, Kanny K.; Shenvi, Ryan A. (Synlett, 2016)
The asmarine alkaloids constitute a small family of terpene-nucleobase marine metabolites defined by a unique N-hydroxy-diazepine pharmacophore that effects moderate to potent cytotoxicity against several cancer cell lines. Isolation of the metabolites from an unidentified producer organism provided enough material for initial assay, but this material was soon exhausted, impeding further study. Procurement of material through synthesis is the obvious solution. Here we chronicle our discovery of simple but potent asmarine analogues that solve the material supply problem.1 Introduction2 Project Selection3 Project Design3.1 The Big Picture3.2 Synthetic Strategy3.3 Challenges in the Design4 The Quest to Find Bioactive Asmarines4.1 Model Systems as Proof of Concepts4.2 Stereoselectivity Investigation with Clerodane-Appended Cyclization Precursors4.2.1 Obtaining the Cyclization Precursor4.2.2 Results from Cyclization Screening4.3 Toward the Synthesis of Asmarine A4.4 A Turning Point: Screening Forward5 Biological Investigation of the Asmarine Scaffold5.1 Cytotoxicity Assays of our Synthetic Intermediates and their Enantiomers5.2 Synthesis of Analogues for a More In-Depth Biological Investigation6 Synthesis of Simple Asmarine Analogues and their Cytotoxicity7 Conclusion
Keywords: antitumor agents; cyclization; ene reaction; natural products; regioselectivity